Pengembangan Computational Thinking Melalui IoT Apps Programming Dengan Tinkercad - Rochadiani, Theresia Herlina; Santoso, Handri; Mayatopani, Hendra (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Computational thinking is one of competencies are needed recently. Most countries had already included computational thinking into their curriculum. Based on PISA 2018, Indonesia placed 72nd ranking of 77 countries for reading, 72nd ranking of 78 countries for mathematics, and 70th ranking of 78 countries for sciences. It is of concern to government and us to elevate this computational thinking ability, especially for students. Through this community service, the training of IoT programming using Tinkercad is given to PAHOA Senior High School students. Theory and hands-on practical in this training was followed by 40 students for 4 months. Based on questionnaire in the end of this training, 62% participations agreed that their computational thinking increase through this training and 96% participations could make IoT apps.